Mindfulness and acceptance : expanding the cognitive-behavioral tradition - Hayes, Steven C.; Follette, Victoria M.; Linehan, Marsha (Online access with DDA: Askews (Medicine), 2004)
"This important volume addresses a new set of behavior therapies developed over the last decade that emphasize such nontraditional themes as mindfulness, acceptance, values, spirituality, being in relationship, focusing on the present moment, and emotional deepening. Offering powerful ways of working with people suffering from difficult clinical issues and challenges, these innovative applications are attracting growing attention from clinicians and researchers alike. From pioneering editors and contributors who thoroughly describe the "whats," "hows," and "whys" of their respective approaches, the book provides the first comprehensive exploration of an increasingly influential movement in contemporary psychotherapy." "This volume will enhance the knowledge and skills of psychotherapists from a range of backgrounds, including clinical psychologists, psychiatrists, clinical social workers, and couple and family therapists, as well as researchers and advanced students in these fields. It will serve as a uniquely informative text in graduate-level courses."--Jacket